SMALL-SCALE PRIMARY SCHOOL TIMETABLING PROBLEM - Yong, Phang How (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study concerns with the primary school timetabling problem (PSTP) of Sekolah Jenis Kebangsaan (C) Peay Min in Pengerang, Johor. School timetabling is to produce a weekly timetable for the school. Most of primary school is manually developed the timetable for each class which is extremely time consuming. The main objective of this study is to propose a two-staged heuristic solution for Primary School Timetabling whereby the algorithm should enable combination of classes from different classes of students and reduce the number of subjects to be taught in a day and develop a simulation model for Primary School Timetabling Problem. Hard constraints of this PSTP are teacher can only teach at one classroom or one subject at a time, allow combination of small classes into one class, limiting number of subjects to be taught in a day, and each subject must satisfy the total weekly period. Soft constraints are spread subject periods into timeslots evenly and solving subject allocation preference periods. A two staged timetabling heuristic approaches are proposed in this study. Clustering is the first phase of this approach which is a method of clustering a set of objects into the same group. It will cluster all subjects into even session and odd session group based on the weekly period of the subject. All subjects will sort into smaller group based on the standard and teacher assigned. Only one subject from standard one to standard six without any repeated teacher is sorted into a same group, except for the case of combining classes. Period allocation is the second phase of this algorithm. Odd session groups will be allocated at the first slot of the day and first slot after recess then followed by even session group in random sequence. From the outcome of the simulation timetabling model, this simulation managed to satisfy all hard constraints and some soft constraints. The simulation shall reduce computational time when computing result and able to generate a clash free practical timetable based on requirements.